High-temperature molten salt corrosion resistant carbon-based coating and preparation method thereof
By using carbon-based coatings prepared by graphite particles, binders and oxide nanopowders, the problems of high-temperature molten salt corrosion-resistant coating materials in the prior art are solved, and efficient corrosion resistance and the effect of reducing production costs are achieved.
Patent Information
- Application Number
- CN202311125857.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, coating materials that resist high temperature molten salt corrosion are expensive, the manufacturing process is complex and the density is poor, making it difficult to apply on a large scale.
Graphite particles are used as the main raw material, combined with binder and oxide nanopowder, and homogenize through magnetic stirring and a high-speed homogenizer to form a coating suspension, and sprayed at room temperature to form a carbon-based coating.
It has achieved improvements in corrosion resistance of high-temperature molten salts, while reducing production costs, good coating density, and effectively reducing corrosion rate.
Smart Images

Figure CN119592146A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high temperature molten salt corrosion resistant coatings, and in particular relates to a high temperature molten salt corrosion resistant carbon-based coating and a preparation method thereof. Background Art
[0002] In the past few decades, anti-corrosion coatings have been widely used to protect metals from corrosion. In recent years, significant progress has been made in many areas of coating technology; these technologies are generally based on the following three mechanisms: 1) the formation of a barrier between the metal substrate material and the surrounding environment; 2) inhibition of the corrosion process; 3) coatings used as sacrificial materials.
[0003] In order to reduce the corrosion of materials such as metals, relevant researchers have developed many technologies on corrosion coatings and coating deposition methods. The selection of coating materials is as important as the selection of compatible coating methods, both of which can achieve the purpose of protecting metals from corrosion. The main criteria for selecting coating materials are usually the effectiveness and cost of the coating, among which the service life (i.e., corrosion rate) under specific application conditions is the primary consideration. The most commonly used components in coating materials are metal materials and ceramic materials. Metal coatings have excellent adhesion, high temperature resistance and high temperature molten salt corrosion resistance, but have defects such as high cost, long manufacturing process cycle, and poor coating density; ceramic coatings have good heat resistance, corrosion resistance, wear resistance and thermal shock resistance, however, their manufacturing process is complicated and easy to peel off. With the continuous research on coating materials, carbon-based materials have attracted more and more attention from academia and industry due to their excellent high temperature resistance and low cost.
[0004] The use of carbon-based materials in anti-corrosion coatings has the advantages of good mechanical and thermal stability, high melting point, airtightness, liquidity, low chemical reactivity and reduced coating thickness. Commonly used carbon-based materials include graphite, graphene, graphene oxide, carbon nanotubes and graphene-based self-healing coatings. Among them, anti-corrosion coatings with graphene as the main component have been widely used to protect metals from corrosion. The main reason is that graphene is the thinnest two-dimensional (2D) carbon material, which can reduce the volume and quantity of the coating, and under the same conditions, its corrosion resistance is better than that of traditional anti-corrosion coatings; however, high manufacturing costs and low production have limited the large-scale application of graphene-based anti-corrosion coatings. Other carbon-based materials except graphene are rarely used in anti-corrosion coating technology. Summary of the invention
[0005] In view of the above-mentioned defects existing in the prior art, the purpose of the present invention is to provide a carbon-based coating resistant to high-temperature molten salt corrosion and a preparation method thereof, which uses graphite particles as the main raw material, and can not only improve the molten salt corrosion resistance, but also reduce the production cost; in terms of corrosion protection, the carbon-based coating increases the thickness of the corrosion rust by sacrificing the coating material, provides protection for metal materials or imposes diffusion restrictions, thereby reducing the corrosion rate.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] A first aspect of the present invention provides a method for preparing a carbon-based coating resistant to high-temperature molten salt corrosion, comprising the following steps:
[0008] S1, heating distilled water and performing magnetic stirring, and gradually adding a binder to the distilled water while maintaining heating and stirring until the binder is completely dissolved to obtain a binder aqueous solution;
[0009] S2, adding graphite particles and oxide nanopowders into the binder aqueous solution, and homogenizing with a high-speed homogenizer to obtain a coating suspension;
[0010] S3, when in use, adding an auxiliary agent to the coating suspension, spraying the coating suspension on a substrate after uniform dispersion, and obtaining a carbon-based coating resistant to high-temperature molten salt corrosion after drying at room temperature.
[0011] Preferably, in step S1:
[0012] The binder is selected from one of latex, cellulose ether and high molecular polymer; and / or
[0013] In the binder aqueous solution, the mass concentration of the binder is 3-20wt.%.
[0014] Preferably, the high molecular weight polymer is polyvinyl alcohol or polyethylene glycol.
[0015] Preferably, the molecular weight of the polyvinyl alcohol is 15,000-30,000.
[0016] Preferably, in the aqueous binder solution, the mass concentration of the binder is 5 to 12 wt.%.
[0017] Preferably, in step S1:
[0018] The distilled water is heated to 70-90° C. and then the binder is added; and / or
[0019] The magnetic stirring uses a magnetic stirring bar, and the rotation speed of the magnetic stirring bar is 500-1000 rpm.
[0020] Preferably, the rotation speed of the magnetic stirrer is 600-700 rpm.
[0021] Preferably, in step S2:
[0022] The graphite particles have a particle size of 1 to 100 μm; and / or
[0023] The oxide nanopowder is aluminum oxide or nano silicon dioxide; and / or
[0024] The particle size of the oxide nanopowder is 1 to 100 nm; and / or
[0025] The rotation speed of the high-speed homogenizer is 5000-20000 rpm.
[0026] Preferably, in step S2, the coating suspension contains:
[0027] The mass concentration of the graphite particles is 10-20wt.%; and / or
[0028] The mass concentration of the oxide nanopowder is 0.1-2 wt.%.
[0029] Preferably, in step S2, the coating suspension contains:
[0030] The mass concentration of the graphite particles is 12-15 wt.%; and / or
[0031] The mass concentration of the oxide nanopowder is 0.5-1 wt.%.
[0032] Preferably, in step S3, the auxiliary agent includes a wetting agent, a thickener, a dispersant and a defoaming agent;
[0033] The usage amount of the wetting agent, thickener, dispersant and defoamer is 0.5-1wt.‰ of the coating suspension.
[0034] Preferably, in step S3, the substrate is one of 304 stainless steel, 304L stainless steel, 316 stainless steel, 316L stainless steel, 321 stainless steel, and 347 stainless steel.
[0035] Preferably, in step S3, the thickness of the carbon-based coating resistant to high-temperature molten salt corrosion is 20 to 150 μm.
[0036] The second aspect of the present invention provides a carbon-based coating resistant to high-temperature molten salt corrosion prepared by the method for preparing a carbon-based coating resistant to high-temperature molten salt corrosion described in the first aspect of the present invention.
[0037] The design principles of the components of the carbon-based coating resistant to high-temperature molten salt corrosion of the present invention are as follows:
[0038] Graphite: It mainly provides a physical and chemical barrier between the molten salt and the substrate, effectively isolating the substrate from the electrolyte. When the carbon-based coating is used, the graphite will undergo an oxidation reaction, which can reduce the transmission rate of oxides in the molten salt to the substrate and form a more compact and adherent oxide layer on the substrate. The oxide layer can further protect the substrate and limit the further diffusion of oxidation products in the molten salt to the substrate, thereby effectively reducing the corrosion rate.
[0039] Binders: Improve molded products to provide handling strength prior to product densification, improve cohesion between graphite particles and adhesion of coatings to metal substrates.
[0040] Oxide nanopowders: used as reinforcement for other coating materials by improving and reducing the porosity of the coating and preventing the penetration of corrosive media.
[0041] Additives: can improve coating performance, promote film formation, and stabilize the suspension state of particles in the coating solution.
[0042] The carbon-based coating resistant to high-temperature molten salt corrosion and the preparation method thereof provided by the present invention have the following beneficial effects:
[0043] 1. The present invention uses graphite as the main raw material of the carbon-based coating, which has good resistance to high-temperature molten salt corrosion and greatly reduces the raw material cost compared with metal and graphene;
[0044] 2. The present invention uses polymer materials as binders (such as water-soluble polymers), which can form and further stabilize particles in solvents, and can be successfully used to prepare slurries for carbon-based coatings on metal surfaces to protect metals from different corrosive environments. The polymer binder has the characteristics of easy preparation and conducive to industrialization;
[0045] 3. The present invention uses graphite with a particle size in the micron range as the main raw material of the carbon-based coating, adds various additives to make the graphite particles evenly adhere to the metal substrate, uses water as the suspension medium, and the product is a water system, which is safe, environmentally friendly, pollution-free, does not contain volatile organic compounds (VOCs), and is easy to construct. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0047] Figure 1 It is a schematic flow chart of a method for preparing a carbon-based coating resistant to high-temperature molten salt corrosion according to the present invention;
[0048] Figure 21 is a surface morphology of a carbon-based coating sprayed on a stainless steel substrate for resisting high-temperature molten salt corrosion in Example 1 of the present invention, (a) is a picture of the carbon-based coating sprayed for resisting high-temperature molten salt corrosion, (b) and (c) are scanning electron microscope (SEM) morphology images of the carbon-based coating sprayed for resisting high-temperature molten salt corrosion;
[0049] Figure 3 The figures are the cross-sectional morphology and EDS elemental analysis of the carbon-based coating sprayed on the stainless steel substrate for resisting high-temperature molten salt corrosion in Example 1 of the present invention; (a) is the cross-sectional morphology of the carbon-based coating sprayed for resisting high-temperature molten salt corrosion, and the thickness of the layer is about 62 μm; the sample is fixed in phenolic resin by heat embedding, and an aluminum film is used to cover the sample surface during the embedding process so that the boundary between the corrosion layer and the phenolic resin in the SEM imaging is obvious, and the morphology of the corrosion layer is easy to observe; (b)-(f) are the cross-sectional EDS elemental analysis results of the carbon-based coating sprayed for resisting high-temperature molten salt corrosion. DETAILED DESCRIPTION
[0050] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with embodiments.
[0051] The main purpose of the present invention is to prepare and apply a carbon-based coating that is resistant to high-temperature molten salt corrosion with an effective temperature of up to 565°C, which can reduce the cost of raw materials and coating methods by about 30 to 50%, and the carbon-based coating that is resistant to high-temperature molten salt corrosion can be used for metal substrates such as stainless steel in a 565°C solar salt environment.
[0052] Combination Figure 1 As shown, the present invention provides a method for preparing a carbon-based coating resistant to high-temperature molten salt corrosion, comprising the following steps:
[0053] S1, heating the distilled water and performing magnetic stirring, and gradually adding a binder to the distilled water while maintaining the heating and stirring until the binder is completely dissolved to obtain a binder aqueous solution;
[0054] Specifically, a glass beaker filled with distilled water is placed on a heater, and a magnetic stirrer is placed in the beaker, and the distilled water is heated to 70-90°C (preferably 90°C). After heating, a binder is gradually added to the distilled water while stirring, and heating and stirring are maintained until the binder is completely dissolved in the distilled water, that is, the solution becomes clear again and the binder particles cannot be seen by the naked eye, and a binder aqueous solution is obtained. The speed of the magnetic stirrer is 500-1000rpm, and in a further preferred embodiment, the speed of the magnetic stirrer is 600-700rpm. The binder is selected from one of latex, cellulose ether and high molecular polymer; the high molecular polymer as a binder is preferably a water-soluble polymer that is easy to form and further stabilize particles in a solvent, such as polyvinyl alcohol (PVA) or polyethylene glycol (PEG), preferably polyvinyl alcohol, the molecular weight of polyvinyl alcohol is 15000-30000, and it can be dissolved in water at 95°C; in the binder aqueous solution, the mass concentration of the binder is 3-20wt.%, and in a preferred embodiment, the mass concentration of the binder is 5-12wt.%.
[0055] S2, adding graphite particles and oxide nanopowders into a binder aqueous solution, and homogenizing with a high-speed homogenizer to obtain a coating suspension;
[0056] Specifically, graphite particles and oxide nanopowders (e.g., alumina, nano-silicon dioxide) are added to a binder aqueous solution, and homogenized for 30±5 minutes using a high-speed homogenizer at room temperature to obtain a coating suspension. The graphite particles are graphite powders with a particle size of 1 to 100 μm; the particle size of the oxide nanopowders is between 1 and 100 nm. In the coating suspension, the mass concentration of the graphite particles is 10 to 20 wt.%, and in a further preferred embodiment, the mass concentration of the graphite particles is 12 to 15 wt.%; in the coating suspension, the mass concentration of the oxide nanopowder is 0.1 to 2 wt.%, and in a further preferred embodiment, the mass concentration of the oxide nanopowder is 0.5 to 1 wt.%. The speed of the high-speed homogenizer is 5000 to 20000 rpm.
[0057] S3, when in use, an additive is added to the coating suspension, and after being evenly dispersed, the coating suspension is sprayed on the substrate, and after drying at room temperature, a carbon-based coating resistant to high-temperature molten salt corrosion is obtained.
[0058] Specifically, when using, wetting agent, thickener, dispersant and defoamer and other additives are added to the coating suspension and stirred and dispersed. After the additives are evenly dispersed in the coating suspension, the coating suspension is sprayed on the substrate using a spray gun, and dried at room temperature (the wet coating takes about 10±2 minutes to dry) to obtain a carbon-based coating resistant to high-temperature molten salt corrosion. The amount of wetting agent, thickener, dispersant and defoamer used is 0.5 to 1wt.‰ of the coating suspension; the wetting agent is preferably Tegotwin4100; the thickener is preferably 0620; the dispersant is preferably Tego 755W; the defoamer is preferably BYK011. The substrate is one of 304 stainless steel, 304L stainless steel, 316 stainless steel, 316L stainless steel, 321 stainless steel, and 347 stainless steel, preferably 347 stainless steel. In a further specific embodiment, the thickness of the carbon-based coating resistant to high-temperature molten salt corrosion is 20 to 150 μm, preferably 80 μm.
[0059] Afterwards, clean the spray gun by adding distilled water to the gun's gravity feed tank and spraying the distilled water onto the paper to verify that no graphite particles are left in the nozzle.
[0060] The present invention also provides a carbon-based coating resistant to high-temperature molten salt corrosion prepared by the above-mentioned method for preparing a carbon-based coating resistant to high-temperature molten salt corrosion. In terms of corrosion behavior, due to the thickening of the corrosion rust, the corrosion rate decreases over time, thus providing a considerable degree of protection and / or applying diffusion restrictions, thereby effectively reducing the corrosion rate. According to the "Test and Evaluation Method for Corrosion of Molten Salt for Solar Thermal Power Generation (T / CSTA 19-2021)", a 3000-hour high-temperature corrosion test was carried out in 565°C solar salt, and the corrosion rate was less than 10 microns / year after 3000 hours.
[0061] The carbon-based coating resistant to high-temperature molten salt corrosion and the preparation method thereof of the present invention are further introduced below with reference to specific examples.
[0062] Example 1
[0063] The carbon-based coating resistant to high-temperature molten salt corrosion and its preparation method in this embodiment are specifically as follows:
[0064] 1) Weigh 47.5 g of distilled water in a beaker and place it on a heater, add a magnetic stirrer, and heat the distilled water to 90°C; after heating, add 2.5 g of polyvinyl alcohol (PVA) gradually while stirring; keep heating and stirring until the solution becomes clear again and the polyvinyl alcohol particles cannot be seen with the naked eye;
[0065] 2) Prepare 10g of 12wt.% graphite, 1wt.% nano-silicon dioxide (nano-SiO 2) and 87wt.% binder solution coating suspension operation process: weigh 1.2g graphite particles, 0.1g nano-silicon dioxide (nano-SiO 2 ), using a pipette to add 8.7 g of the binder solution prepared in step 1), and using a high-speed disperser to homogenize at a speed of 10000 rpm for half an hour to obtain 10 g of a coating suspension;
[0066] 3) When using, add 1wt.‰ wetting agent, 0.5wt.‰ thickener, 1wt.‰ dispersant, 0.5wt.‰ defoamer and other additives to the coating suspension, add the coating suspension in step 2) to the gravity feed tank of the spray gun, spray the 347 stainless steel plate with the coating suspension using the spray gun, and stop spraying the coating suspension when all samples are coated. It takes about 10 minutes for the sample to touch dry, and a carbon-based coating with a thickness of 60μm that is resistant to high-temperature molten salt corrosion is obtained.
[0067] 4) Clean the spray gun and add distilled water to the gravity feed tank. Spray the distilled water onto the paper to confirm that no graphite particles are left in the nozzle.
[0068] 5) The steel plate coated in step 3 was subjected to a high temperature corrosion resistance test in a solar salt environment at 565° C. for 1000 hours. The test results are shown in Table 1.
[0069] Figure 2 (a) shows a macroscopic photograph of three 347 stainless steel samples after being sprayed with a carbon-based coating and dried. Figure 2 (b) and (c) are scanning electron microscope (SEM) surface images of 347 stainless steel coated samples, showing a dense and uniform coating composed of graphite particles and binder as well as oxide nanopowder.
[0070] like Figure 3 (a) shows a cross-sectional scanning electron microscope image of 347 stainless steel with a carbon-based coating, showing that the coating is densely attached to the substrate surface. The sample was fixed in phenolic resin by heat embedding and polished successively using silicon carbide papers of different particle sizes, and finally polished using a diamond suspension with a particle size of 1 micron. During the embedding process, an aluminum film was used to cover the sample surface to make the corrosion layer more obvious in SEM imaging. Figure 3 (b) shows the corresponding energy dispersive spectroscopy (EDS) elemental mapping, highlighting the enrichment of carbon and silicon in the coating.
[0071] Example 2
[0072] The carbon-based coating resistant to high-temperature molten salt corrosion and its preparation method in this embodiment are specifically as follows:
[0073] 1) Weigh 45g of distilled water in a beaker and place it on a heater, add a magnetic stirrer, and heat the distilled water to 85°C; after heating, add 5g of polyvinyl alcohol (PVA) gradually while stirring; keep heating and stirring until the solution becomes clear again and the polyvinyl alcohol particles cannot be seen with the naked eye;
[0074] 2) Prepare 10g of 10wt.% graphite, 0.5wt.% nano-silicon dioxide (nano-SiO 2 ) and 89.5wt.% binder solution coating suspension operation process: weigh 1g graphite particles, 0.05g nano-silicon dioxide (nano-SiO 2 ) adding 8.95 g of the binder solution prepared in step 1) using a pipette to obtain 10 g of a coating suspension;
[0075] 3) When using, add 1wt.‰ wetting agent, 0.5‰wt.‰ thickener, 1wt.‰ dispersant, 0.5wt.‰ defoamer and other additives to the coating suspension, add the coating suspension in step 2) to the gravity feed tank of the spray gun, spray the 347 stainless steel plate with the coating suspension using the spray gun, and stop spraying the coating suspension when all samples are coated. It takes about 10 minutes for the sample to touch dry, and a carbon-based coating with a thickness of 60μm that is resistant to high-temperature molten salt corrosion is obtained.
[0076] 4) Clean the spray gun and add distilled water to the gravity feed tank. Spray the distilled water onto the paper to confirm that no graphite particles are left in the nozzle.
[0077] 5) The steel plate coated in step 3 was subjected to a high temperature corrosion resistance test in a solar salt environment at 565° C. for 1000 hours. The test results are shown in Table 1.
[0078] Example 3
[0079] The carbon-based coating resistant to high-temperature molten salt corrosion and its preparation method in this embodiment are specifically as follows:
[0080] 1) Weigh 47g of distilled water in a beaker and place it on a heater, add a magnetic stirrer, and heat the distilled water to 80°C; after heating, add 3g of polyvinyl alcohol (PVA) gradually while stirring; keep heating and stirring until the solution becomes clear again and the polyvinyl alcohol particles cannot be seen with the naked eye;
[0081] 2) Prepare 10g of 15wt.% graphite, 1wt.% nano-silicon dioxide (nano-SiO 2 ) and 84wt.% binder solution coating suspension operation process: weigh 1.5g graphite particles, 0.1g nano-silicon dioxide (nano-SiO 2) adding 8.4 g of the binder solution prepared in step 1) using a pipette to obtain 10 g of a coating suspension;
[0082] 3) When using, add 1‰wt.% wetting agent, 0.5‰wt.% thickener, 1‰wt.% dispersant, 0.5‰wt.% defoamer and other additives to the coating suspension, add the coating suspension in step 2) to the gravity feed tank of the spray gun, spray the 347 stainless steel plate with the coating suspension using the spray gun, and stop spraying the coating suspension when all samples are coated. It takes about 10 minutes for the sample to touch dry, and a carbon-based coating with a thickness of 60μm that is resistant to high-temperature molten salt corrosion is obtained.
[0083] 4) Clean the spray gun and add distilled water to the gravity feed tank. Spray the distilled water onto the paper to confirm that no graphite particles are left in the nozzle.
[0084] 5) The steel plate coated in step 3 was subjected to a high temperature corrosion resistance test in a solar salt environment at 565° C. for 1000 hours. The test results are shown in Table 1.
[0085] Table 1 Related parameters in the embodiment
[0086] Example 1 Example 2 Example 3 graphite 1.2 1 1.5 Polyvinyl alcohol 0.435 0.895 0.504 water 8.265 8.055 7.896 Nano Silica 0.1 0.05 0.1 Wetting Agents 0.01 0.01 0.01 Thickener 0.005 0.005 0.005 Dispersants 0.01 0.01 0.01 Defoaming agent 0.005 0.005 0.005 Solid content 17.30% 19.40% 20% Particle size 11.7μm 13.2μm 15.7μm Corrosion rate 8.8μm / year 9.2μm / year 9.1μm / year
[0087] As shown in Table 1, the corrosion rate of the carbon-based coating resistant to high-temperature molten salt corrosion prepared in the embodiment of the present invention is less than 10 μm / year after 1000 hours in a solar salt environment at 565°C.
[0088] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.
Claims
1. A method for preparing a carbon-based coating resistant to high-temperature molten salt corrosion, characterized in that: The following steps are involved: S1, heating distilled water and performing magnetic stirring, and gradually adding a binder to the distilled water while maintaining heating and stirring until the binder is completely dissolved to obtain a binder aqueous solution; S2, adding graphite particles and oxide nanopowders into the binder aqueous solution, and homogenizing with a high-speed homogenizer to obtain a coating suspension; S3, when in use, adding an additive to the coating suspension, spraying the coating suspension on a substrate after uniform dispersion, and obtaining a carbon-based coating resistant to high-temperature molten salt corrosion after drying at room temperature.
2. The method for preparing a carbon-based coating resistant to high temperature molten salt corrosion according to claim 1, characterized in that: In step S1: The binder is selected from one of latex, cellulose ether and high molecular polymer; and / or In the binder aqueous solution, the mass concentration of the binder is 3-20wt.%.
3. The method for preparing a carbon-based coating resistant to high temperature molten salt corrosion according to claim 2, characterized in that: The high molecular polymer is polyvinyl alcohol or polyethylene glycol.
4. The method for preparing a carbon-based coating resistant to high temperature molten salt corrosion according to claim 3, characterized in that: The molecular weight of the polyvinyl alcohol is 15000-30000.
5. The method for preparing a carbon-based coating resistant to high temperature molten salt corrosion according to claim 2, characterized in that: In the binder aqueous solution, the mass concentration of the binder is 5 to 12 wt.%.
6. The method for preparing a carbon-based coating resistant to high temperature molten salt corrosion according to claim 1, characterized in that: In step S1: The distilled water is heated to 70-90° C. and then the binder is added; and / or The magnetic stirring uses a magnetic stirring bar, and the rotation speed of the magnetic stirring bar is 500-1000 rpm.
7. The method for preparing a carbon-based coating resistant to high temperature molten salt corrosion according to claim 6, characterized in that: The rotation speed of the magnetic stirrer is 600-700 rpm.
8. The method for preparing a carbon-based coating resistant to high temperature molten salt corrosion according to claim 1, characterized in that: In step S2: The particle size of the graphite particles is 1 to 100 μm; and / or The oxide nano powder is aluminum oxide or nano silicon dioxide; and / or The particle size of the oxide nanopowder is 1 to 100 nm; and / or The rotation speed of the high-speed homogenizer is 5000-20000 rpm.
9. The method for preparing a carbon-based coating resistant to high temperature molten salt corrosion according to claim 1, characterized in that: In the step S2, in the coating suspension: The mass concentration of the graphite particles is 10-20wt.%; and / or The mass concentration of the oxide nanopowder is 0.1-2 wt.%.
10. The method for preparing a carbon-based coating resistant to high temperature molten salt corrosion according to claim 9, characterized in that: In the step S2, in the coating suspension: The mass concentration of the graphite particles is 12-15 wt.%; and / or The mass concentration of the oxide nanopowder is 0.5-1 wt.%.
11. The method for preparing a carbon-based coating resistant to high temperature molten salt corrosion according to claim 1, characterized in that: In step S3, the auxiliary agent includes a wetting agent, a thickening agent, a dispersant and a defoaming agent; The usage amount of the wetting agent, thickener, dispersant and defoamer is 0.5-1wt.‰ of the coating suspension.
12. The method for preparing a carbon-based coating resistant to high temperature molten salt corrosion according to claim 1, characterized in that: In step S3, the substrate is one of 304 stainless steel, 304L stainless steel, 316 stainless steel, 316L stainless steel, 321 stainless steel, and 347 stainless steel.
13. The method for preparing a carbon-based coating resistant to high temperature molten salt corrosion according to claim 1, characterized in that: In the step S3, the thickness of the carbon-based coating resistant to high-temperature molten salt corrosion is 20 to 150 μm.
14. A carbon-based coating resistant to high-temperature molten salt corrosion prepared by the method for preparing a carbon-based coating resistant to high-temperature molten salt corrosion according to any one of claims 1 to 13.
Citation Information
Patent Citations
Process for providing metallic substrates with corrosion resistance
CN105008466A
Production of corrosion resistant coatings for metals comprises applying metallic or non-metallic inorganic nano-particulate powder in an organic matrix onto the metal surface, removing the organic matrix, and sintering
DE19939686A1
Method for forming an electrically conductive multilayer coating with Anti- corrosion properties onto a metallic substrate
US20210125748A1